Considerations about the use of lime-cement mortars for render conservation purposes - Pacheco-Torgal, F. (2011)
Some investigations about conservation renders points out that Portland cement based mortars should be avoided and should be replaced by lime-pozzolan mortars. However, this type of mortar is still under investigation and the majority of Portuguese construction enterprises operating in the field of building conservation do not possess enough know-how about them. Besides the absolute rejection of the use of Portland cement based mortars even with just a minimum amount appears to be a dogmatic position that is not fully grounded in scientific terms. These facts can influence the decision about the material’s choice for conservation purposes, since in certain circumstances it may be preferable to apply blended mortars instead of an incorrect application of lime-pozzolan mortars.